Inclusive Excellence in Practice: Integrating Equitable, Consequential Learning and an Inclusive Climate in Higher Education Classrooms and Institutions - Davis, Susannah; Nolen, Susan; Koretsky, Milo (Frontline Learning Research, 2024)
In education, initiatives aimed at improving diversity, equity, inclusivity, and justice (DEIJ) are often conceptualized and implemented separately from those addressing students’ and faculty’s learning — and the reverse is also true. In this theoretical paper with an empirical illustration, we present a holistic framework based on our experience with a comprehensive change initiative. The I2 Framework posits that DEIJ and learning goals need to be addressed simultaneously and at multiple, intersecting organizational levels. Through a systems approach, I2 integrates change activity across two dimensions: one representing goals of reform (DEIJ and improved learning) and another representing levels of organizational change (classroom and department/organization). I2 integrates the work of creating equitable, consequential learning opportunities in the classroom and the work of creating an inclusive climate at the departmental/organizational level, emphasizing their inherent relatedness. We provide an empirical example based on design-based implementation research and related mixed methods analyses of a multi-year change project in an engineering department at a large, public university in the United States. The example highlights a need to shift the nature of this work, how we do this work, and the environment and culture within which we do this work at both the classroom level and the department level. The example also illustrates ways that elements of the change initiative intersected with existing institutional practices, leading some innovations to succeed and others to be resisted. The I2 Framework provides guidance to practitioners, policymakers, and leaders working towards equitable, consequential learning at the classroom level and an inclusive climate at departmental and institutional levels.